Self-Reported Sleep and Executive Function in Early Primary School Children - Chen, Yulu; Wang, Yiji; Wang, Si; Zhang, Ming; Wu, Nan (Frontiers in Psychology, 2021)
The study investigated the associations between children’s self-reported habitual sleep disturbance and multidimensional executive function (EF). Two hundred and four 7- to 9-year-old typically developing children completed the Sleep Self-Report, and finished the Red-Blue Test, Wisconsin Card Sorting Test and Backward Digit Span Test, indexing different EF components including inhibitory control, cognitive flexibility and working memory. Results revealed that all the three EF components were significantly correlated with sleep. However, cognitive flexibility was no longer significantly related to sleep when the other EF components—inhibitory control and working memory—were controlled for. Meanwhile, inhibitory control, as well as working memory, was still significantly related to sleep after controlling for the other EF components. Results suggest that children’s self-reported sleep might be associated directly with inhibitory control and working memory, but indirectly with cognitive flexibility.